Theoretical And Practical Analysis Of Dry Friction Processes In Mechanical Systems (Diversity Research: Journal of Analysis and Trends, 2026)
Dry friction is an essential component of mechanical systems and represents the resisting force that arises between bodies in the absence of a lubricating medium. This topic analyzes the theoretical foundations of dry friction, in particular the Amontons–Coulomb laws and their limitations of applicability. The dependence of the friction coefficient on material properties, surface roughness, and external conditions is studied. In addition, the differences between static and kinetic friction and their influence on the stability of mechanical systems are examined. From a practical perspective, the role of dry friction in machines and mechanisms, as well as its effects on energy losses and wear processes, is analyzed. The results of the study are important for improving the efficiency of mechanical systems and extending their service life. Furthermore, modern modeling methods are discussed as a means of achieving a more accurate representation of friction phenomena. This topic is considered highly relevant for the fields of mechanics and engineering